A pilot randomised controlled trial of Problem‐Solving Treatment for Visual Impairment (POSITIVE): protocol paper. (July 2014) - Riazi, Afsane; Walters, Kate; Rubin, Gary; Ambler, Gareth; Jichi, Fatima; Mynors‐Wallis, Laurence; O'Driscoll, Miriam; Stephen, Jacqueline; Aspden, Trefor
Abstract Purpose For visually impaired individuals, motivation to be mobile and the individual's emotional states are predetermining factors of functioning. In addition, loss of confidence at the time of diagnosis could inhibit the ability to make progress. The aim of this study is to evaluate whether Problem‐Solving Treatment, a brief, structured psychological intervention, leads to better psychological well‐being in people who have been recently diagnosed as blind or partially sighted. Methods A pilot randomised controlled trial: the trial aims to recruit 120 individuals who have either: (1) been diagnosed with severe, irreversible sight loss, or (2) registered as blind or partially sighted within the last 3 months. Individuals will be randomly allocated to either the intervention or control group with randomisation stratified by severity of vision loss. Those in the intervention arm will receive Problem‐Solving Treatment, an established intervention that addresses individual's confidence, motivation and psychological well‐being by undertaking specific tasks to help individuals work through their problems, and recognising steps to problem resolution. Both groups will continue to receive routine care, such as mobility training. Study Outcomes The primary outcome is psychological well‐being measured at 3, 6, and 9 months after recruitment and assignment to intervention or control group. Secondary outcomes include symptoms of distress, mobility and quality of life.